(3cJGH aj GdaQb Hjf GdCeQGV GdeTJHgI aj GdWHs ((3YHO GdbGOQ Hf NjQ GdOjf Hf CHGjRjO s)
(3ChdgG (B:s
(3GdMeO ddg GdPi gOGfG heG cfG dfgJOi dhdG Cf gOGfG Gddg CeG HYO aEfi deG QCjJ CWHGA GdReGf dGjYQahf ef GdCeQGV ZdGeG JUhQhG Yf GdcJH HOGFdg hCSHGHg s
(3BNQgG (B:s
(3Ef cGf CHjV agh Odjd GdPHhd hEf cGf CMeQ agh Odjd GdCMJQGb Je GdCaJQGb GdCeQGV HYhf Gddg s
(3GdcJGH ef JUfjaGJ UGMH eGdGjSY ai GdaQb Hjf GdCeQGV GdeTJHgIs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs